Do Role of Program TV and Host Attractiveness Influence the Interest of Watching? A Case of Indonesian Program TV and Indonesian Public Figure - Surianto Surianto; Frenky Frenky; Yesica Yuliani Clara; Destri Sari Gunarti (Jurnal Impresi Indonesia, 2026)
This study examines the influence of television program characteristics and host attractiveness on viewers’ viewing intention using the Indonesian television program Lapor Pak! on TRANS7 as the research context. A quantitative survey was conducted involving 97 respondents selected through purposive sampling. Data were collected using structured questionnaires and analyzed using multiple linear regression analysis. The findings reveal that television program characteristics have a positive and statistically significant effect on viewers’ viewing intention. Host attractiveness also has a positive and significant influence and demonstrates a stronger contribution than television program characteristics. Simultaneously, both independent variables significantly affect viewing intention and explain 64.7% of its variance. These findings indicate that engaging television program characteristics and attractive hosts with strong communication competence complement each other in increasing audience interest. This study contributes to the broadcasting communication literature by providing empirical evidence regarding the combined role of program characteristics and host attractiveness in shaping television viewing behavior and offers practical implications for broadcasters in developing competitive television programs.